Perlindungan Konsumen Pengguna Kartu E – Toll Yang Hilang Dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Christoffer Immanuel Hutapea; Bima Kumara Dwi Atmaja (Universitas Pahlawan Tuanku Tambusai, 2024)
The objective of this research is to investigate the safeguarding of E-Toll users' interests cards that are lost from the perspective of consumer protection laws. This study employs a normative legal research method with a legislative approach. The study's findings indicate that there is a legal vacuum concerning the protection of consumers using E-Toll cards that are lost; therefore, the foundation of consumer protection is not enforced. The regulation of consumer protection is under the jurisdiction of Law Number 8 of 1999 without specific or detailed provisions regarding this matter. Other regulations that can be found in Bank Indonesia Regulation Number: 20/6/PBI/2018 on Electronic Money.